Book Review of: Mark Solovey, Christian Dayé: Cold War Social Science - Fontaine, Philippe (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Solovey, Mark, and Christian Dayé (Eds.) (2021) Cold War Social Science: Transnational Entanglements, Cham: Palgrave Macmillan. 400 pp. ISBN:978-3-030-70245-8 Price: $126,59